Changes in maximum muscle torque of knee joint extensor muscles depending on various forms of warm-up in the training microcycle - Szyszka, P. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to determine the changes of maximum muscle torque of knee joint extensor muscles under static conditions in the training microcycle using different protocols of warm-up exercises. The study included 5 training units in the preparatory period. The test procedure included 2 measurements during one training unit. The first measurement was taken before the warm-up, the second after the end of the warm-up, and before starting the proper part of the training. During the performance of individual training units, specific warm-up protocols were applied to 15 weightlifters.